Minding the Baby®: Enhancing parental reflective functioning and infant attachment in an attachment-based, interdisciplinary home visiting program. (February 2020) - Slade, Arietta; Holland, Margaret L.; Ordway, Monica Roosa; Carlson, Elizabeth A.; Jeon, Sangchoon; Close, Nancy; Mayes, Linda C.; Sadler, Lois S.
Abstract: In this article, we describe the results of the second phase of a randomized controlled trial of Minding the Baby (MTB), an interdisciplinary reflective parenting intervention for infants and their families. Young first-time mothers living in underserved, poor, urban communities received intensive home visiting services from a nurse and social worker team for 27 months, from pregnancy to the child's second birthday. Results indicate that MTB mothers' levels of reflective functioning was more likely to increase over the course of the intervention than were those of control group mothers. Likewise, infants in the MTB group were significantly more likely to be securely attached, and significantly less likely to be disorganized, than infants in the control group. We discuss our findings in terms of their contribution to understanding the impacts and import of intensive intervention with vulnerable families during the earliest stages of parenthood in preventing the intergenerational transmission of disrupted relationships and insecure attachment.